A Technology–Organisation–Environment (TOE) - based m-business value instrument - Picoto, Winnie Ng (2022)
Mobile business (m-business) creates new business opportunities. Yet, existing research focuses on customer adoption factors rather than an assessment of the value of m-business for organisations. This study fills this gap through the development of a conceptual model of m-business value at the organisational level, which is grounded in the technology–organisation–environment (TOE) framework and the resource-based view (RBV) theory. The model suggests seven determinants of m-business use and value: technology readiness, firm size, managerial obstacles, competitive pressure, regulatory environment, partner pressure, and mobile environment. M-business value is a second order construct comprising the impact on downstream dimensions (e.g., sales support, customer service, market growth), on internal dimensions (e.g., internal processes, staff productivity), and on upstream dimensions (e.g., procurement, coordination with suppliers). This study develops an instrument to assess m-business usage and value. Data collected from 111 professionals is then used to test the proposed instrument. Implications and contributions are discussed.